A better mousetrap to guard against anthracnose disease in bean. (4th May 2021) - Cannon, Steven B; Innes, Roger W
Abstract : This article comments on: Richard MSM, Gratias A, Alvarez Diaz JC, Thareau V, Pflieger S, Meziadi C, Blanchet S, Marande W, Bitochi E, Papa R, Miklas PN, Geffroy V . 2021. A common bean truncated CRINKLY4 kinase controls gene-for-gene resistance to the fungus Colletotrichum lindemuthianum . Journal of Experimental Botany 72, 3569–3581 .